2019
DOI: 10.1186/s13049-019-0673-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of NICE or SNC guidelines may reduce the need for computerized tomographies in patients with mild traumatic brain injury: a retrospective chart review and theoretical application of five guidelines

Abstract: BackgroundTraumatic brain injuries continue to be a significant cause of mortality and morbidity worldwide. Most traumatic brain injuries are classified as mild, with a low but not negligible risk of intracranial hemorrhage. To help physicians decide which patients might benefit from a computerized tomography (CT) of the head to rule out intracranial hemorrhage, several clinical decision rules have been developed and proven effective in reducing the amount of negative CTs, but they have not been compared again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…This is time-consuming, expensive and exposes the patient to potentially harmful radiation [ 14 , 15 ]. The annual ED influx of head-trauma patients is substantial [ 7 , 21 , 25 ]. Even small improvements in the clinical management that lead to decreased processing time, decreased use of radiation and/or decreased cost due to the use of brain biomarkers and other diagnostic tools, such as microwave machines, would benefit the health care system and patients alike [ 7 , 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is time-consuming, expensive and exposes the patient to potentially harmful radiation [ 14 , 15 ]. The annual ED influx of head-trauma patients is substantial [ 7 , 21 , 25 ]. Even small improvements in the clinical management that lead to decreased processing time, decreased use of radiation and/or decreased cost due to the use of brain biomarkers and other diagnostic tools, such as microwave machines, would benefit the health care system and patients alike [ 7 , 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that patients with trauma to the head who are Glasgow Coma Scale (GCS) 13-15 do not have an increased risk of cervical spine injury [26]. A previous study by Vedin et al [7,21,25] at Helsingborg General Hospital on a very similar patient cohort has shown that approximately 99% of the patients are GCS 13-15. Hence, the theoretical risk of aggravating a pre-existing cervical spine injury is very low with this study design.…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Several guidelines have been developed and shown good validity in identifying patients at risk of significant intracranial injury, but have often been wrongfully applied [7][8][9][10]. A study conducted by our group indicated that computerised tomographies (CT) following TBIs could be reduced with strict guideline adherence [11]. Another study that we conducted regarding perceived and actual adherence to guidelines for managing patients with TBI in the emergency department (ED) showed low levels of adherence and frequent guideline misinterpretation.…”
Section: Introductionmentioning
confidence: 99%